2014
DOI: 10.1007/s10493-014-9866-z
|View full text |Cite
|
Sign up to set email alerts
|

Purification of vitellin and dynamics of vitellogenesis in the parthenogenetic tick Haemaphysalis longicornis (Acari: Ixodidae)

Abstract: Vitellin (Vt) was purified from eggs of parthenogenetic bush tick Haemaphysalis longicornis by gel filtration and ion exchange chromatography. Our results revealed that only one single Vt existed in parthenogenetic bush tick, and the purified Vt was proved to be a hemoglycolipoprotein consisting of nine polypeptides with molecular weights of 203, 147, 126, 82, 74, 70, 61, 47 and 31 kDa, respectively. Polyclonal antibody and monoclonal antibody against Vt were produced using the purified Vt. The change in vitel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Clathrin heavy chain involved in endocytic pathway regulates expression of vitellogenin in R. haemaphysaloides (Kuang et al, 2020). Vitellin is a hemoglycolipoprotein consisting of many bands (James and Oliver, 1997;Yang et al, 2015). Similarly, there were 11 polypeptides of vitellin identified by proteomic analysis in the R. haemaphysaloides ticks and vitellin antibody in this study recognized two bands of 136 and 72 kDa ( Supplementary Figure 4) that is different from the peptides of vitellogenin in ovary proteomics analysis (Supplementary Tables 4, 5), resulting in inconsistent phenomenon.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Clathrin heavy chain involved in endocytic pathway regulates expression of vitellogenin in R. haemaphysaloides (Kuang et al, 2020). Vitellin is a hemoglycolipoprotein consisting of many bands (James and Oliver, 1997;Yang et al, 2015). Similarly, there were 11 polypeptides of vitellin identified by proteomic analysis in the R. haemaphysaloides ticks and vitellin antibody in this study recognized two bands of 136 and 72 kDa ( Supplementary Figure 4) that is different from the peptides of vitellogenin in ovary proteomics analysis (Supplementary Tables 4, 5), resulting in inconsistent phenomenon.…”
Section: Discussionmentioning
confidence: 70%
“…We speculated that RH36 was involved in the integration of nutrition and reproduction in ticks, in which vitellogenin is critical to tick ovary maturation since it serves as the nutritional source for tick survivability and reproduction (Xavier et al, 2018). Vitellogenin and vitellin are structurally, biochemically and immunologically similar in the majority of insects, including ticks, which results in McAb against vitellin recognized vitellogenins (Kaufman, 2004;Yang et al, 2015). Four vitellogenin genes ( Supplementary Figure 1) and McAb against vitellin (Figure 4) were obtained to test the dynamics of vitellogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although both cathepsin B and D were indicated to regulate embryogenesis, their dynamic changes were not the same in the parthenogenetic and bisexual populations. In our previous work, we found that the vitellin of the parthenogenetic population exhibits 9 subunits, ranging from 31 kDa to 203 kDa; however, in the bisexual population, vitellin exhibits only 8 subunits, ranging from 52 kDa to 112 kDa [44,45]. This might be another reason for the different dynamic changes in the enzymes, in addition to the longer incubation period.…”
Section: Discussionmentioning
confidence: 92%